Volume 1: Turbomachinery 1998
DOI: 10.1115/98-gt-244
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of Impeller–Volute Interaction in Centrifugal Compressors

Abstract: A numerical procedure to predict the impeller/volute interaction in a single-stage centrifugal compressor is presented. The method couples a three-dimensional unsteady flow calculation in the impeller with a three-dimensional time-averaged flow calculation in the volute through an iterative updating of the boundary conditions on the interface of both calculation domains. The method has been used to calculate the flow in a compressor with an external volute at off-design operation. Computed circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 8 publications
1
31
0
Order By: Relevance
“…Wavelike pressure perturbations are caused by the volute tongue; hence, the frequency f can be set as the rotational speed N . Distortion waves of higher frequency, as they were discussed in references [11] and [30], cannot be predicted using the frozen rotor approach. A simulation applying the frozen rotor model is an exact representation of the flow field only in case the Strouhal number is close to zero.…”
Section: Rotor-stator Interactionmentioning
confidence: 99%
“…Wavelike pressure perturbations are caused by the volute tongue; hence, the frequency f can be set as the rotational speed N . Distortion waves of higher frequency, as they were discussed in references [11] and [30], cannot be predicted using the frozen rotor approach. A simulation applying the frozen rotor model is an exact representation of the flow field only in case the Strouhal number is close to zero.…”
Section: Rotor-stator Interactionmentioning
confidence: 99%
“…However, regarding centrifugal compressors, the literatures pay attention on the impeller-diffuser-volute interaction. [9][10][11] In Park and Cimbala's 12 experiments, they found that the two slots configuration outperforms the one slot configuration in rapid wake decay. Corcoran's 13 work showed that the trailing-edge blowing reduces the Reynolds stress, the vorticity and the velocity fluctuations within one chord length downstream.…”
Section: Introductionmentioning
confidence: 99%
“…The last decade research becomes more sophisticated, specifically recently, Hillewaert et al [11], Gonzalez et al [12][13][14], Byskov et al [15], Meakhail et al [16], Majidi [17] and Feng et al [18] extended the prediction of the performance at various operating conditions, different from the normal one, taking into account the dynamic effects of the flow.…”
Section: Introductionmentioning
confidence: 99%